The application of the Cynefin framework in disaster risk management: Predictive approaches for enhancing practices and adaptive approaches to address complexity and uncertainty - Fernandes , Samir Batista (Seven Editora, 2023)
Effective disaster management is critical to ensuring the safety and well-being of communities. In this context, this work aimed to analyze the importance of Cynefin as a tool that can improve the response to natural disasters, addressing the different dimensions that the Cynefin framework offers from the gaps identified in the simulations carried out in the state civil defense of Rio de Janeiro. To achieve this objective, a methodological approach was used that involved the analysis of the simulations, the application of the Cynefin framework and interviews with the participants. The results obtained revealed some gaps in the organization of the simulations, in the communication between the participants and in the evaluation of the results. The use of the Cynefin framework proved to be an adaptive and guiding approach that contributed to dealing with the complexity and uncertainty of disasters. From the analysis carried out, practices were identified that can be adopted to improve the organization, such as the implementation of the Deming cycle for the predictive domain, the approach and the Snowden approach for the adaptive domain.. In summary, this work presents valuable insights and practical directions to improve disaster management practices, aiming at the safety and well-being of the population. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-009